Система представления предметно-ориентированных знаний для создания "умного" предприятия на основе интеллектуальных средств обработки и онтологических подходов - Лещенко, В.А.; Морозова, А.И.; Таран, Л.Ю. (Управляющие системы и машины, 2016)
Представлена система, обеспечивающая развитие «умного» предприятия на основе новых концепций, подходов, методов и технологий. Рассмотрена общая база знаний системы, ее структура, предметное наполнение и интеллектуальные модели, поддерживающие базу знаний в актуализированном состоянии. Представлено систему, що забезпечує розвиток «розумного» підприємства на основі нових концепцій, підходів, методів і технологій. Розглянуто загальну базу знань системи, її структуру, предметне наповнення та інтелектуальні моделі підтримання бази знань в актуалізованому стані. The computer system knowledge base is presented, ensuring the development of the "smart" enterprise due to the accumulation of knowledge on the new concepts, approaches, methods and technologies of business management. Knowledge base structure is subject-oriented. A company with its objectives and "smart" enterprise (SE) as a computer system that provides automation and the intellectualization management system are considered in the role of "domains". Update of knowledge base is performed by means of knowledge obtained from the external sources. Scientific articles, speeches, various reports and documents, technical product documentation, descriptions of the entire systems and their components provided by the external standards and regulations documenting systems may act in the role of the external sources. These standards and regulations are developed and used by the system as the basic concepts of the formalization of knowledge extracted from outside sources, and the external representation existing in the system of knowledge about the SE. The processes of extracting knowledge from the external sources, their structuring, formalization and representation are associated with the processing of knowledge through approaches, methods and tools at the disposal of knowledge engineering. Ontology is used for the integral representation of the knowledge system. A model of extracting and structuring knowledge was developed by the authors using communicative methods, where an expert acts as a source of knowledge, and textual methods, where a scientific paper acts the role of a source of knowledge. This creates more patterns of extraction and representation of knowledge contained in the printed sources such as interviews and other external sources, taking into account their specificity. They have a common methodological framework, are built on the same principles, and share the same approaches and methods. Despite the fact, that the models are developed as independent ones, they are intended to common coordinated functioning within the systems that implement specific objectives for the different situations. Knowledge extracted by such models always constitutes a comprehensive knowledge system having both verbal and formal representation and algorithms converting one form to another.